Analysis and design of long span beam sections up to 40 metre / Mohd Zainal Abidin Yusof - Yusof, Mohd Zainal Abidin (1990)
The aim of this project is to develop a model in designing long span beams. By referring to the model, the beam sizes and the area of reinforcement can easily be determined provided that the loadings and span are known. Emphasis were given to Reinforced Concrete and Prestressed Concrete design. Spreadsheets were prepared to aid the design based on British Code of Practice, BS 8110 : 1985. All analysis were made on the results obtained from the spreadsheets. Discussions, were done on how the area of reinforcement, breadth and depth of beam changes with the variation of span and loading.